1972
DOI: 10.1111/j.1471-4159.1972.tb03824.x
|View full text |Cite
|
Sign up to set email alerts
|

TRANSPORT OF l‐TRYPTOPHAN INTO SLICES OF RAT CEREBRAL CORTEX1

Abstract: —Slices of rat cerebral cortex, when incubated aerobically at 37°C in Krebs‐Ringer‐phosphate solution (pH 7.0) containing 10 mm glucose and 1.0 mm l‐tryptophan [1‐14C], accumulated tryptophan. Within the first 15 min of incubation the ratio of the concentration of the amino acid in the tissue to that in the medium reached 3.5:1. Uptake of tryptophan was linear for the first 30 min and attained a maximum concentration ratio (tissue:medium) of 6.5:1 within 60 min. The transport mechanism became saturated at 1.0‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

1974
1974
1988
1988

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…(b) Competition between tryptophan and a group of neutral amino acids for uptake by the brain This has been shown in vitro (Kiely & Sourkes, 1972) and in vivo (Oldendorf, 1971). The tryptophan concentrations used in these experiments were considerably greater than those of free tryptophan in plasma.…”
Section: Introductionmentioning
confidence: 86%
“…(b) Competition between tryptophan and a group of neutral amino acids for uptake by the brain This has been shown in vitro (Kiely & Sourkes, 1972) and in vivo (Oldendorf, 1971). The tryptophan concentrations used in these experiments were considerably greater than those of free tryptophan in plasma.…”
Section: Introductionmentioning
confidence: 86%
“…This is probably because it competes with tryptophan for uptake into the brain, since kynurenine decreases accumulation of labelled tryptophan in brain slices Kiely & Sourkes, 1972) and decreases rat brain tryptophan 1 h following injection. Thus the finding that this compound had no effect on brain tryptophan concentrations and did not decrease brain 5-HT or 5-HIAA concentrations in the gerbil again indicates differences in tryptophan metabolism between these two rodents.…”
Section: Discussionmentioning
confidence: 99%
“…The high plasma kynurenine concentration attained during chronic tryptophan treatment is of particular interest as Green & Curzon (1970) and Kiely & Sourkes (1972) both found that kynurenine interfered with tryptophan transport into rat brain. The experiments of Gal et al (1978) in the rat suggest that the plasma concentrations observed in the current study might well cause a lowering of the amount of tryptophan transported into the brain.…”
Section: T-imentioning
confidence: 99%